Cover Stories: Concealing Speciesist Violence in U.S. News Reporting on the COVID-19 “Pork” Industry Crisis - Barca, Lisa A. (Frontiers in Communication, 2022)
With a focus on journalistic discourse, this paper argues for a re-envisioning of food-system communication that takes non-human animals into account as stakeholders in systems that commodify them. This is especially urgent in light of the global pandemic, which has laid bare the vulnerability to crisis inherent in animal-based food production. As a case study to illustrate the need for a just and non-human inclusive orientation to food-systems communication, the paper performs a qualitative rhetorical examination, me critical discourse analysis and critical animal studies, of a series of articles in major U.S. news sources in May of 2020, a few months into the economic shutdown in the U.S. in response to the COVID-19 pandemic. At that time, millions of pigs were brutally killed on U.S. farms due to the impossibility of killing them in slaughterhouses overrun with COVID-19 outbreaks. The analysis finds that media reporting legitimated violence against pigs by framing narratives from industry perspectives, deflecting agency for violence and presenting pigs as willing victims, masking violence through euphemism, objectifying pigs and ignoring their sentience, and uncritically propagating industry rhetoric about “humane” farming. Through these representations, it is argued, the media failed in their responsibility to present the viewpoints of all sentient beings affected by the crisis; in other words, all stakeholders. The methodology merges a textually-oriented approach to critical discourse analysis (CDA) with social critique informed by critical animal studies (CAS), and the essay concludes with recommendations for journalists and other food-system communicators, which should be possible to implement even given the current capitalist, industry-influenced media environment and the demonstrated ruthlessness of animal industries in silencing voices inimical to their profitmaking.